Study of insulin status in metabolic syndrome in correlation with presence of other risk factors - Shekhar, Sudhanshu; Singh, Ram Ranjan; Akhtar, Md. Jawed; Shankar, Vijay (International Journal of Research in Medical Sciences, 2017)
Background: The metabolic syndrome or insulin resistance syndrome is widely prevalent and multifactorial disorder. The majority of persons with metabolic syndrome have insulin resistance. Insulin resistance and / or associated hyperinsulinemia are believed to be the direct cause of other metabolic syndrome risk factors. The present work is being done to assess the insulin status and to assess the correlation between insulin status and other component of metabolic syndrome. Methods: The present work is being carried out in 112 cases of metabolic syndrome, defined as per modified NCEP ATP III (MS-4) criteria. Serum insulin of all cases was measured by chemiluminescent microparticle immunoassay (CMIA) technique. Results: It was observed that 62% of the patients of metabolic syndrome had elevated serum insulin level (Hyperinsulinemia). Hyperinsulinemia was found to be significantly associated with diastolic hypertension and HDL in males. A high association was also noted with BMI. Insulin resistance (HOMA-IR >2.50) was significantly associated with waist circumference in males (p value<0.05). Conclusions: It was observed that metabolic syndrome is associated with elevated serum insulin levels and each component of metabolic syndrome, both biochemical as well as clinical, is associated with hyper-insulinemia and this reflects the presence of insulin resistance in subjects of study.